2011
DOI: 10.3960/jslrt.51.29
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Clinical Outcomes of CHOP Chemotherapy between Japanese Patients with Nodal Peripheral T-Cell Lymphomas and Those with Diffuse Large B-Cell Lymphoma in the Study Group of the Tohoku Hematology Forum

Abstract: To clarify the clinical outcome of peripheral T-cell lymphomas (PTCLs), we conducted a retrospective review comparing the outcomes of patients with PTCL (nodal peripheral T-cell lymphoma, unspecified, n=34 ; angioimmunoblastic T-cell lymphoma, n=12) to those with diffuse large B-cell lymphoma (DLBCL, n=48). All patients received CHOP-based chemotherapy without rituximab. PTCL patients presented at a more advanced clinical stage (91% vs. 65%, P < 0.002) with a poorer performance status (26% vs. 17%, P<0.002) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…An increasing number of research studies suggest that etoposide has been used in intensive chemotherapy regimens, such as cisplatin, etoposide, gemcitabine, and solumedrol (PEGS), and L-asparaginase and etoposide (SMILE) for PTCL 25,26. Indeed, as a standard therapy for PTCL, most patients treated with CHOP will achieve a CR ranging from 31%–69%27 or a CR + PR of 48% 28. Notably, a study has demonstrated that the ORR and CR for evaluable non-Hodgkin’s lymphoma patients was significantly increased in CHOPE group compared to CHOP group (ORR: 82.5% vs 62.5%; CR: 52.5% vs 45%), respectively 29.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of research studies suggest that etoposide has been used in intensive chemotherapy regimens, such as cisplatin, etoposide, gemcitabine, and solumedrol (PEGS), and L-asparaginase and etoposide (SMILE) for PTCL 25,26. Indeed, as a standard therapy for PTCL, most patients treated with CHOP will achieve a CR ranging from 31%–69%27 or a CR + PR of 48% 28. Notably, a study has demonstrated that the ORR and CR for evaluable non-Hodgkin’s lymphoma patients was significantly increased in CHOPE group compared to CHOP group (ORR: 82.5% vs 62.5%; CR: 52.5% vs 45%), respectively 29.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral T-cell lymphomas (PTCLs) are a rare and heterogeneous group of mature T-cell lymphomas that are usually characterized by aggressive clinical behavior, and a paucity of salvage therapies, especially in contrast to their B-cell counterparts [Akagi et al. 2011; Puig et al.…”
Section: Introductionmentioning
confidence: 99%
“…The peripheral T-cell lymphomas (PTCLs) are a rare and heterogeneous group of mature T-cell lymphomas that are usually characterized by aggressive clinical behavior, and a paucity of salvage therapies, especially in contrast to their B-cell counterparts [Akagi et al 2011;Puig et al 2013;Hamadani et al 2014]. The outcome of frontline chemotherapy regimens has been disappointing, with reported long-term survival of only 20-30% [Hamadani et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of PVRL is extranodal, non-Hodgkin, diffuse large B-cell lymphoma (DLBCL) [4]. Although rare, T-cell lymphoma with intraocular involvement has also been reported, usually with poor prognosis [57]. …”
Section: Introductionmentioning
confidence: 99%